2021
DOI: 10.1002/cphc.202100059
|View full text |Cite
|
Sign up to set email alerts
|

The Permeation Mechanism of Cisplatin Through a Dioleoylphosphocholine Bilayer**

Abstract: The investigation of the intermolecular interactions between platinum-based anticancer drugs and lipid bilayers is of special relevance to unveil the mechanisms involved in different steps of the anticancer mode of action of these drugs. We have simulated the permeation of cisplatin through a model membrane composed of 1,2-dioleoyl-sn-glycero-3-phosphocholine lipids by means of umbrella sampling classical molecular dynamics simulations. The initial physisorption of cisplatin into the polar region of the lipid … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 69 publications
0
6
0
Order By: Relevance
“…Due to the biological relevance of phosphatidylcholine lipids, DOPC and DPPC membranes are widely chosen as models in experimental and computational investigations. DOPC was chosen as a lipid unit by our group in previous studies of membrane permeability with very satisfactory results in comparison with the available experimental data [ 21 , 23 ]. The membrane was built with the help of the CHARMM-GUI website [ 24 ].…”
Section: Methodsmentioning
confidence: 99%
“…Due to the biological relevance of phosphatidylcholine lipids, DOPC and DPPC membranes are widely chosen as models in experimental and computational investigations. DOPC was chosen as a lipid unit by our group in previous studies of membrane permeability with very satisfactory results in comparison with the available experimental data [ 21 , 23 ]. The membrane was built with the help of the CHARMM-GUI website [ 24 ].…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, membrane fluidity plays a major role in the mechanism of passive diffusion. To function properly, cell membranes must retain fluidity to permit molecular transport into or out of the cell [33]. It was recently suggested that decreased membrane fluidity may affect cisplatin transport into cells while being the main cause of the resistance mechanism and inefficient uptake by target cells [34].…”
Section: Bzimu Cluster Formationmentioning
confidence: 99%
“…Ruano et al reported the permeation mechanism of cddp through a membrane model formed by 1,2-dioleoyl-sn-glycero-3-phosphocholine (DOPC) lipids. 18 The potential of mean force (PMF) calculated displayed a barrier of only 0.2 kcal mol −1 to the cddp insertion in the polar heads region of the biomembrane, and an energy barrier of 10.4 kcal mol −1 to reach the hydrophobic center. Nierzwick et al also showed an energy barrier of 12.0 kcal mol −1 for cddp to enter the center of a 1,2-dimyristoyl-sn-glycero-3-phosphocholine (DMPC) membrane, thereby indicating a high repulsion to this drug immersed in the lipid tails region.…”
Section: Introductionmentioning
confidence: 99%
“…The Pt(II)-based drug uptake can be also approached by molecular dynamics (MD) simulations, thereby providing important insights and explanations of the cellular transport at the molecular level. Ruano et al reported the permeation mechanism of cddp through a membrane model formed by 1,2-dioleoyl- sn -glycero-3-phosphocholine (DOPC) lipids . The potential of mean force (PMF) calculated displayed a barrier of only 0.2 kcal mol –1 to the cddp insertion in the polar heads region of the biomembrane, and an energy barrier of 10.4 kcal mol –1 to reach the hydrophobic center.…”
Section: Introductionmentioning
confidence: 99%